Environmental fate descriptors for glycol-coated selenium nanoparticles: a quantitative multi-assay approach. Issue 12 (4th November 2019) - Chaudhary, Savita; Chauhan, Pooja; Kumar, Rajeev
Abstract : The application of selenium nanoparticles (Se-NPs) in the fields of biological and physical science is escalating very fast. Abstract : The application of selenium nanoparticles (Se-NPs) in the fields of biological and physical science is escalating very fast. Therefore, it is necessary to investigate the effects of Se-NPs for their prospective vulnerability in the environment. The present work involved the investigation of the toxicological responses of four different types of glycols, i.e., EG, DEG, TEG and PEG coated on Se-NPs by using a multi-assay approach. The influence of the surface-coated Se-NPs was examined over four different types of bacterial strains. Additional work was carried out with glycol-coated Se-NPs for observing their anti-oxidative activities. To achieve the objective of assessing the environmental fate of the chosen Se-NPs, they were tested for assessing their hydrogen peroxide free radical scavenging activity and total reduction behaviour. The in vitro stability of the surface-coated Se-NPs was investigated over various components of blood. It was observed from the data that 15% glycol-encapsulated Se-NPs were biocompatible with the chosen components. The sorption, degradation and aggregation parameters were investigated to describe the environmental fate of the surface-coated Se-NPs. The results from the multi-assay activities are meaningful for improving the perception about the ecological fate of Se-NPs with their probable threats and reducing the uncertainty about their use.